Subjective reward processing and catechol-O- methyltransferase Val158Met polymorphism as potential research domain criteria in addiction: A pilot study - Rohlfing, Nico; Bonnet, Udo; Tendolkar, Indira; Hinney, Anke; Scherbaum, Norbert (Frontiers in Psychiatry, 2022)
The goal of the Research Domain Criteria (RDoC) approach is to grasp mental functioning in continuous valid dimensions from functional to pathological. Reward processing is a transdiagnostic functioning domain of the RDoC. Due to prototypical abnormalities, addictions are especially applicable for the investigation of reward processing. Subjective reward processing is challenging to determine and differs between genotypes of the Catechol-O-methyltransferase gene (COMT) Val158Met polymorphism for incomparable daily life experiences. Thus, we implemented the Monetary Incentive Delay (MID) Task with comparable reward cues and Visual Analog Scales (VAS) to assess subjective reward processing in male abstinent cannabis dependent individuals (N=13) and a control group of nicotine smokers (N=13). COMT Val158Met genotypes were nominally associated with differences in cigarettes smoked per day and motivation in the MID Task (p = 0.028; p = 0.017). For feedback gain, activation of the right insula was increased in controls and activation correlated with gain expectancy and satisfaction about gain. Subjective value is not detached from reward parameters, but is a systematic quotient between value and cue parameters. The underlying neural mechanisms are a fundamental target point for treatments, interventions and cognitive behavioral therapy.